ANTIFUNGAL POTENTIAL OF BARK EXTRACTS FROM BRAZILIAN SEMI-ARID TREE SPECIES AGAINST Ganoderma spp. - Silva, Thiago Cardoso; Braz, Rafael Leite; Araujo, Emmanoella Costa Guaraná; Silva, Gisely Alves da; Palha, Maria de Los Angeles Perez Fernandez (Floresta, 2024)
Tree native species of the Caatinga (a Brazilian semi-arid biome) have characteristics of interest for the use of their wood and non-wood products, especially regarding their natural chemical compounds. The aim of this study was to evaluate the antifungal action of different bark extracts of Anacardium occidentale, Ziziphus joazeiro and Mimosa caesalpiniifolia against Ganoderma lobatum and G. multiplicatum by in vitro mycelial inhibition. The extractions from the bark of the trees were carried out with a Soxhlet extractor, using water, ethanol and hexane as solvents. The potential of mycelia inhibition of each extract was tested against fungi of the Ganoderma genus. The hexane extracts of the bark had activity against G. multiplicatum, unlike the aqueous and ethanol extracts. Even though the hexane-based extracts had a small mycelial inhibition effect against G. lobatum, there were no satisfactory results of extracts against this fungus species.